2020
DOI: 10.2478/helm-2020-0030
|View full text |Cite
|
Sign up to set email alerts
|

Helminth parasites of fish of the Kazakhstan sector of the Caspian Sea and associated drainage basin

Abstract: SummaryThe northern section of the Caspian Sea is an important fishery for Kazakhstan. In the present study, a total of 606 individuals of 13 fish species were collected. For each of Abramis brama, Alosa saposchnikowii, Atherina boyeri caspia, Carassius auratus, Clupeonella cultriventris, Cyprinus carpio, Liza aurata, Leuciscus aspius, Rutilus rutilus caspius, Sander lucioperca, Sander marinus, and Sander volgensis 50 individuals were examined whilst 6 individuals of Siluris glanis were examined. The nematode … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 11 publications
0
3
0
1
Order By: Relevance
“…Until recently, the parasite was only detected in marine ichthyofauna, but recently there have been increasing reports of anisakids in freshwater fish close to the coast (Dana et al 2018;Falla-Zuñiga et al 2021;Ozuni et al 2021). Similar reports apply to rivers in the Caspian Basin (Pilin et al 2014;Abdybekova et al 2020;Zhatkanbaeva et al 2021;Nurzhanova et al 2022). Predominantly Nurzhanova et al (2022), Zhatkanbaeva et al (2021) and Pilin et al (2014) reported the presence of anisacid larvae in predatory fish such as perch, pike, and zander.…”
Section: Discussionmentioning
confidence: 83%
“…Until recently, the parasite was only detected in marine ichthyofauna, but recently there have been increasing reports of anisakids in freshwater fish close to the coast (Dana et al 2018;Falla-Zuñiga et al 2021;Ozuni et al 2021). Similar reports apply to rivers in the Caspian Basin (Pilin et al 2014;Abdybekova et al 2020;Zhatkanbaeva et al 2021;Nurzhanova et al 2022). Predominantly Nurzhanova et al (2022), Zhatkanbaeva et al (2021) and Pilin et al (2014) reported the presence of anisacid larvae in predatory fish such as perch, pike, and zander.…”
Section: Discussionmentioning
confidence: 83%
“…All fish were collected in late spring to early summer. These included 450 fish collected in 2018 reported in a preliminary study (Abdybekova et al ., 2020). The species composition of the fish was determined on the basis of taxonomic descriptions according to Berg (1949), Kazancheyev (1981) and Reshetnikova (2002).…”
Section: Methodsmentioning
confidence: 99%
“…Such studies may also contribute to ameliorating the public health risk of some helminths as some species such as the asp and pike perch may be heavily infected with Anisakis spp. (Abdybekova et al ., 2020).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…его улов на Каспии составлял около 2,5 тыс. тонн в год [1,2]. В последующие годы численность морского судака на Каспии резко снизилась.…”
Section: Introductionunclassified